Preventive Effects of an Enriched Environment on Rodent Psychiatric Disorder Models - Kazuhiro Takuma; Yukio Ago; Toshio Matsuda (Elsevier, 2011)
Abstract.: Interplay between genetic and environmental factors plays a key role in psychiatric disorders, as well as other brain diseases, cancer, and metabolic syndrome. In accordance with epidemiological findings, animal studies have pointed out the importance of a variety of environmental factors, such as viral infection during pregnancy or infancy, early parental loss or separation, and physical or sexual abuse in early life, in the etiology of psychiatric disorders. Conversely, positive effects of environmental factors against the pathogenesis of psychiatric disorders are also demonstrated, in which most of the animals are exposed to an "enriched environment". This review summarizes recent progress of research in this field focusing on the preventive effects of an "enriched environment" against the expression of behavioral abnormalities in rodent models of psychiatric disorders. Keywords:: psychiatric disorder, gene-environmental interaction, environmental enrichment